Views and Experiences of Dementia in People With Intellectual Disabilities: A Systematic Review of Qualitative Research. - Carter, Joanna; Spector, Aimee; Ali, Afia; McFeeters, Amelia; Butt, Sarah; Charlesworth, Georgina (Journal of Intellectual Disability Research, 2025)
Background: It is important to hear the perspectives of people with intellectual disabilities on dementia. This review aimed to explore views and experiences of dementia from the perspective of people with intellectual disabilities and methodologies enabling people with intellectual disabilities and dementia to participate in qualitative research. Methods: Studies were identified in database searches, along with reference and citation searches. Qualitative data were reviewed using thematic synthesis and risk of bias assessed using the Critical Appraisal Skills Programme (2018). Methodologies used to include participants with intellectual disabilities and dementia were reviewed. Results: Findings from 11 studies, with a total of 47 participants, highlighted loss of ability, relationships and connection associated with dementia, counteracted by support from others, and maintenance of a sense of self through choice, relational connection and competence. A range of methodologies were identified to enable participants with intellectual disabilities and dementia to participate in research. Conclusions: This review highlights emerging, albeit demographically limited, qualitative research in this field. It suggests ways to build on this including methodologies to facilitate inclusion of people with intellectual disabilities and dementia in further research.